Study of the Acoustic Suitability of an Open Plan Office Based on STI and DL2 Simulations - PASSERO, Carolina Reich Marcon; ZANNIN, Paulo Henrique Trombetta (Archives of Acoustics, 2012)
Many business offices around the world are organized as open plan offices. Therefore, studies about the acoustic comfort of the people who work in them have become increasingly important. The focus of this work is the acoustic evaluation of an open plan office combining several architectural characteristics and levels of ambient noise. This evaluation was performed through a computational model calibrated from a real office. The rate of spatial decay of sound pressure levels per distance doubling (DL2) and the speech transmission index (STI) were simulated for the acoustic evaluation of the office, allowing for the determination of the radius of distraction (rD). These parameters were simulated for 6 situations using different floor and ceiling covering materials and inserting or withdrawing screens between workstations. In addition, STI and rD were simulated under two conditions of ambient noise. The results indicated that the DL2 and rD are adequate acoustic parameters for the acoustic evaluation and improvement of an open plan office. The DL2 was strongly influenced by the presence or absence of screens between workstations and by the ceiling covering material. The rD was more sensitive to changes in ambient noise.